The Role Of Locus Of Control Toward Arousal Procrastination Among Students - Thoyyibatus Sarirah; Paramita Apsari (Universitas Katolik Soegijapranata, 2019)
This study aims to determine the role of locus of control toward arousal procrastination among students. This study involved 400 students from Universitas Brawijaya. The sampling technique used accidental sampling.The measuring instrument used in this study is The Multidimensional Locus of Control IPC Scale (1981) to measure students' locus of control and the measuring instrument for arousal procrastination is adapted from General Procrastination Scale (GPS) Lay (1986). Data analysis using multiple linear regression analysis. Research result shows locus of control simultanneously contribute to arousal procrastination with signinificance of 0,001 (p < 0,05). Where the locus of control takes effect as much as 3,6 % toward arousal procrastination, the other 96,4 % is explained by other factors. According to the partial test, there are not found any role of the internal locus of control and external chance toward the arousal procrastination, however, a significant positive role is found on the external powerfull other toward arousal procrastination among students.